Qualidade da água de cactáceas e seu potencial para aproveitamento - Aquino, Yara Caroline (Universidade Federal Rural do Semi-Árido, 2017)
Water scarcity occurs in many regions of the world and Brazil, providing the various communities to daily coexistence with this lack. Given the uncertainty regarding the incidence of rainfall and high evaporation rates in some regions of Brazil, the study of plants with lower water requirements and high storage capacity may be an alternative for these regions. The drought for being prolonged and constant in the northeastern semi-arid region motivated this study. With the objective of analyzing the water quality of two cactaceous species, palma (Opuntia-ficus indica Mill) and mandacaru (Cereus jamacaru D.C.), and to evaluate its potential for use in dry periods. The study was carried out using physicochemical and microbiological analyzes for the evaluation of water quality for human and animal consumption. The two species presented strong similarities regarding water storage and physicochemical analysis behavior, and indicated quality outside the potability standards for human consumption.
Keywords: Plantas; armazenamento de água; estiagem; plants; water storage; drought; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA